ETIKA PROFESSIONAL DAN RUH AGAMA DI AWAL MILLENIUM - Abd. Rachman Mas‘ud (Sekretariat Badan Litbang dan Diklat Kementerian Agama RI, 2017)
The concept of professional ethics is partly comprised of what a professional should or should not do in the work place. It also encompasses a much greater part of the professionals life. If a professional is to have ethics then that person needs to adopt that conduct in all of his dealings. There are professional codes of ethics to consider and adopt in the way professionals conduct themselves in and out of the work place. This article explaines things that are included in professional ethichs, consist of concepts like: efficiency, professionalism, working well, little waste, diligence, punctuality, frugality, humbleness, spirit of prestige, need for achievement, open-minded, self-discipline and responsibility, self-reliance and the interpretation of religious thoughts. These ethics will be the basis of national development and needs to be reidentified in this 21st century.